Trouble call analysis for single and multiple outages in radial distribution feeders - Subedi, Laxman (Kansas State University, 2012)
Outage management describes system utilized by electric distribution utilities to help restore power in event of an outage. The complexity of outage management system employed by different utilities to determine the location of fault could differ. First step of outage management is to know where the problem is. Utilities typically depend on customers to call and inform them of the problem by entering their addresses. After sufficient calls are received, the utility is able to pinpoint the location of the outage. This part of outage management is called trouble call analysis. In event of fault in a feeder of a radial distribution system, the upstream device or the device that serves to protect that particular zone activates and opens the circuit. This particular device is considered as the operated protective device. The knowledge of the activated protective device can help locate the fault. Repair crews could be sent to that particular location to carry out power restoration efforts. The main objective of this work is to study model of distribution system that could utilize the network topology and customer calls to predict the location of the operated protective device. Such prediction would be based on the knowledge of the least amount of variables i.e. network topology and customer calls. Radial distribution systems are modeled using the immune system algorithm and test cases with trouble calls are simulated in MATLAB to test the effectiveness of the proposed technique. Also, the proposed technique is tested on an actual feeder circuit with real call scenarios to verify against the known fault locations.
Keywords: Trouble Calls; Distribution System; Radial Feeders; Outages; Outage Management; Electrical Engineering (0544)